Efektivitas Pelatihan Pencegahan dan Pengendalian Penyakit Tidak Menular terhadap Efikasi Diri Kader Posyandu: The Effectiveness of Training on Non-Communicable Disease Prevention and Control toward the Self-Efficacy of Posyandu Cadres - Suharsono, Suharsono; Isworo, Adi; Ashar N, Novema (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Non-Communicable Diseases (NCDs) are the main causes of morbidity and death in Indonesia. Prevention and control of PTM requires the active role of Pos Pelayanan Terpadu (Posyandu) cadres. However, low self-efficacy of cadres often becomes an obstacle in carrying out these tasks. Therefore, the aim of this community service is to increase the capacity and self-efficacy of cadres in efforts to prevent and control NCDs. This community service uses a participatory training approach aimed at increasing cadres' self-efficacy. A total of 30 cadres were selected as respondents through purposive sampling techniques. Inclusion criteria include active cadres in posyandu, aged 20–60 years, and willing to take part in the entire series of training. Activities were carried out in the form of intensive training which includes material delivery, group discussions, simulations and evaluation. Self-efficacy measurements were carried out before and after the intervention using the General Self-Efficacy (GSE) questionnaire. Data analysis was applied to see changes in cadre self-efficacy categories before and after training. The results of this activity showed that at the time of the pretest, most of the cadres were in the medium category, 21 people (70%) and 4 people low (13.3%). After the training, there was a significant increase in the good self-efficacy category, namely to 20 people (66.7%) and there were no cadres in the low category with a p value = 0.001. It can be concluded from this community service activity that participatory-based training can increase the self-efficacy of Posyandu cadres in preventing and controlling NCDs.